Evaluation of neurotrophic factor secreting mesenchymal stem cells in progressive multiple sclerosis. (January 2023) - Cohen, Jeffrey A; Lublin, Fred D; Lock, Christoper; Pelletier, Daniel; Chitnis, Tanuja; Mehra, Munish; Gothelf, Yael; Aricha, Revital; Lindborg, Stacy; Lebovits, Chaim; Levy, Yossef; Motamed Khorasani, Afsaneh; et al.
Background: Autologous mesenchymal stem cell neurotrophic factor–secreting cells (NurOwn ® ) have the potential to modify underlying disease mechanisms in progressive multiple sclerosis (PMS). Objective: This open-label phase II study was conducted to evaluate safety/efficacy of three intrathecal cell treatments. Methods: Eighteen participants with non-relapsing PMS were treated. The primary endpoint was safety. Secondary endpoints included: cerebrospinal fluid (CSF) biomarkers; timed 25-foot walk speed, nine-hole peg test (9-HPT), low-contrast letter acuity, symbol digit modalities test, and 12-item multiple sclerosis (MS) walking scale. Seventeen participants received all treatments. Results: No deaths/adverse events related to worsening of MS, clinical/magnetic resonance imaging (MRI) evidence of disease activation, and clinically significant changes in safety lab results were reported. Two participants developed symptoms of low back and leg pain, consistent with a diagnosis of arachnoiditis, occurring in one of three intrathecal treatments in both participants. Nineteen percent of treated participants achieved pre-specified ⩾ 25% improvements in timed 25-foot walk speed/nine-HPT at 28 weeks compared to baseline, along with consistent efficacy signals for pre-specified response criteria across other secondary efficacy outcomes. CSF neuroprotective factors increased, and inflammatory biomarkers decreased after treatment, consistent with the proposed mechanism of action. Conclusion: Based on these encouraging preliminary findings, further confirmation in a randomized study is warranted.